Study On Components Rating Of Gasoline Engine As A Performance Quality Indicator Of Lemigas Formulated Api Sl Lubricant - Setyo Widodo; Shinta Sari H; Catur Yuliani R; Subiyanto Subiyanto (Scientific Contributions Oil and Gas, 2010)
Poor lubrication may cause wear on the surface moving parts of engine components such as bearings due to the metal-to-metal contact. Engine components utilized on the road-test of gasoline engine’s lubricating oil API SL showed wear and tear on some parts of them. The sum of wear occurred during the road test were varied. Therefore, an analysis of wear quantity of engine’s components was a necessity in order to get information about lubrication condition on engine. Analysis of wear was conducted by components’ rating based on the standard specifications set out for performance level of lubricant oil API SL and ILSAC GF-3 (SNI 06-7069-2005). Analysis based on Seq. IIIF showed that average value of the piston skirt varnish is 10, low temperature viscosity is 4673 cP, and cam wear lifter is 0.002 mm. It was also showed that the minimum kinematics viscosity increase was managed to be stay-in-grade. Analysis based on Seq. IVA showed that the average value of cam wear is 0.0015 mm. Analysis based on Seq. VII showed that the value of bearing weight loss was 0.010 g and there was no deposit at high temperatures. Shear stability analysis based on Seq. VIII showed that the viscosity of lubricant oil is still in the range of allowed values.